Teaching Materials or Speaking Skills in the Book “Al Arabiyyah Baina Yadaik” - Ritonga, Nur'ainun; Maksudin, Maksudin; Muhajir, Muhajir; Musthofa, Tulus; Setiyawan, Agung (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the instructional materials for speaking skills in the book Al-Arabiyyah Baina Yadaik for first-year students, parts one and two. This library research uses a qualitative approach and a descriptive method, with documentation used as the data collection technique. The method of data analysis employed is content analysis. The primary data sources are the book Al-Arabiyyah Baina Yadaik for first-year students, parts one and two, and the book Pembelajaran Konstruktivisme, Teori dan Aplikasi Pembelajaran dalam Pembentukan Karakter by Sigit Mangun Wardoyo. Secondary sources include books, previous research findings, and scientific articles related to the topic. The findings of this study show that the instructional materials for speaking skills are presented in the form of dialogues between two or more people, covering 16 dialogue topics. Each unit contains three dialogues, except for the first unit, which contains six dialogues. The materials align with two out of the seven characteristics of constructivist theory but are less aligned or not aligned with the others.